Vibration effects of loads due to groups crossing a lively footbridge. (2017) - Hawryszków, Paweł; Pimentel, Roberto; Silva, Felipe
Abstract: The suitability of the group load for vibration serviceability of footbridges in vertical direction is analysed. The rationale is that the more pedestrians are on a footbridge the more the actual effect of the presence of pedestrians as dynamic systems is relevant for the vibration response. Therefore, it is expected that, by increasing the number of pedestrians, representing pedestrians only as loads would diverge from reality. To investigate this matter, measured responses from controlled tests of crossings of single and of groups of pedestrians on a two span cable-stayed footbridge were compared to respective results from simulations using a calibrated finite element (FE) model of the structure. The step frequency was controlled by a metronome, to reduce variability such as getting out of rhythm or differences of phase among pedestrians walking in group. In the 3-D FE model, the loads were represented by means of classical Fourier Series since the pacing rate was controlled in all tests. First, the results of the single crossings of each pedestrian were employed to obtain the dynamic load factor for that pedestrian. In sequence, the same comparison was made between the measured and simulated responses of the group. As the level of acceleration increased when comparing the results from group with the individual crossings, the effect of the presence of pedestrians as dynamic systems were more significant in the former, providing evidence that modeling the pedestrians as dynamic systems is needed for this load case.